Варіант оптимізації витрат на систему захисту інформації - Заболотний, В. І.; Петросян, К. С. (ХНУРЭ, 2008)
Organization of restricted access information during the information activity starts from problem definition of information security. There are three variants of problem definition. It is recommended to provide information security by one of variants depending on information owner. One of the variants is based on conscious allowance such level of information security which causes loses of unprotected data not more than all enterprise income.
Keywords: оптимізація витрат; система захисту інформації